The Intellectual Insights in Forensic Investigations of Airplane Accidents - Alkhatib, Ahed J (PSM Biological Research, 2025)
Forensic evidence plays a critical role in determining the cause of an airplane crash. Such evidence can range from individual problems with materials and sub-systems that lead to catastrophic failure, to performance anomalies, design issues and flawed regulations. The goal of this essay is to explore the role of forensic evidence in a series of aviation accidents with the purpose of de-emphasizing notions of culpability and competences of the crew as the primary causes of crashes. It suggests a wider application of forensic science also to structures and systems surrounding the aircraft, and hence a more multidisciplinary response to the issues of contemporary aviation safety. The improvement in the latter and the prevention of future incidents ought to be the common goal of the aviation industry, regulatory bodies, passengers and general public. The discussion is structured around the basic principles of the inquiry conducted by the forensic investigator. The main focus is on the three types of evidential consideration in a typical forensic account: physical (deconstructive analysis, expert examination of the airframe wreckage, aircraft systems and engines), environmental (consideration of the wider airline operation, strategic aspects of company policy, weather, air traffic control), and systemic causes (structural and organizational issues at the level of airline management, regulatory bodies, government, procedures and standards in the sphere of air travel). There is a potential discussion of the wider types of evidence within each of these categories that becomes the context of an exposition, in real-life detail, of the various contributing factors within the aforementioned planes dynamics.